The Effect of Incentives and Work Stress on Employee Performance during the Covid-19 Pandemic at PTPN IV Plantation Land - Fajar Rezeki Ananda Lubis; Vina Winda Sari (Jurnal Mantik, 2022)
This study aims to determine the effect of incentives and work stress on employee performance during the COVID-19 pandemic. This research was conducted at Kebon Tanah Raja PTPN IV. The number of samples in this study were 51 people. Data was collected using a questionnaire in accordance with the indicators of each variable used. The data obtained were then analyzed using multiple linear regression analysis. The results show that incentives and work stress simultaneously have a significant effect on employee performance during the COVID-19 pandemic. The results of the t test show that incentives and work stress have a significant effect on employee performance. Incentive factors have a more dominant influence on employee performance compared to work stress.